Improving Seed Viability and Vigor of Acacia crassicarpa A. Cunn. Ex Benth. Using Ultrafine Bubbles and Biopriming Based on Dark Septate Endophytes - Dede Jajat Sudrajat; Evayusvita Rustam; Mohammad Agus Salim; Yulianti; Nurhasybi; Naning Yuniarti; Surono; Yohanes Aris Purwanto (Department of Forestry, Faculty of Agriculture, University of Lampung, 2026)
Acacia crassicarpa is a fast-growing tree species that has been a mainstay in the establishment of industrial plantation forests in Indonesia. The need for A. crassicarpa seedlings for large-scale planting programs is often hampered by poor seed germination due to strong dormancy and low seed vigor. This study aims to analyze the effects of ultrafine bubbles (UFB) and biopriming with dark septate endophytes (DSE) on the viability and vigor of A. crassicarpa seeds. Before treatment, all seeds were soaked in 98% H2SO4 for 15 minutes as a field procedure for A. crassicarpa seed germination, serving as the positive control in this study. A completely randomized factorial design with two factors, i.e., UFB water (0, 8, and 20 ppm) and DSE isolates (without DSE, MM15 (DSE MM.15), Cladosporium teunissimum (DSE KSP.1), and Dendrothyrium sp. (DSE CPP.114), was used to test the effects of the treatments on seed germination parameters (germination capacity, germination speed, germination value, hypocotyl and radicle length, and vigor index). The germination parameters were analyzed using analysis of variance and Duncan’s Multiple Range Test at the 95% confidence level. The interaction between UFB and DSE treatments significantly affected germination capacity, germination speed, germination value, and vigor index. The optimal result was achieved by soaking seeds in 8 ppm UFB water for 24 hours, combined with soaking in DSE CPP.114 for 24 hours with a germination capacity of 78.5% (increase of 32.5% from control), germination speed of 8.04% day-1 (increase of 38% from control), germination value of 15.39 (increase of 188.7% from control), and vigor index of 11.29 (increase of 80.3% from control). Thus, the UFB water and DSE Dendrothyrium sp. (DSE CPP.114) can increase seed viability and vigor after scarification, thereby directly improving the quality and quantity of A. crassicarpa seedlings for planting programs. Keywords: Acacia crassicarpa, biopriming, dark septate endophyte, seed germination, ultrafine bubbles